Resposta :
Oie, tudo bom?
a)
[tex]y = 6x - 1 \\ 0 = 6x - 1 \\ - 6x = - 1 \: . \: ( - 1) \\ 6x = 1 \\ \boxed{x = \frac{1}{6} }[/tex]
b)
[tex]y = \frac{7}{3} x \\ 0 = \frac{7}{3} x \\ 0 = \frac{3}{7} \: . \: \frac{7}{3} x \\ 0 = x \\ \boxed{x = 0}[/tex]
c)
[tex]y = - 6x + 60 \\ 0 = - 6x + 60 \\ 6x = 60 \\ x = \frac{60}{6} \\ \boxed{x = 10}[/tex]
d)
[tex]y = - 1,6x \\ 0 = - 1,6x \\ - 1,6x = 0 \\ x = - \frac{0}{1,6} \\ \boxed{x = 0}[/tex]
e)
[tex]y = 3x + 6 \\ 0 = 3x + 6 \\ - 3x = 6 \: . \: ( - 1) \\ 3x = - 6 \\ x = - \frac{6}{3} \\ \boxed{x = - 2}[/tex]
f)
[tex]y = - \frac{1}{7} x + 2 \\ 0 = - \frac{1}{7} x + 2 \\ 0 = - 7 \: . \: \frac{1}{7} x + 7 \: . \: 2 \\ 0 = - x + 14 \\ \boxed{x = 14}[/tex]
Att. NLE Top Shotta